Definitions influence for digital photocamera parameters of calibration on transformation of photos in the plane - Sužiedelytė-Visockienė, Jūratė (Geodesy and Cartography, 2012)
Nowadays for close-range photogrammetric works digital cameras are applied. In the article the calibrations of camera Canon EOS 350D are submitted. Internal parameters of a camera are determined. They concern symmetric and asymmetric distortion of a digital camera. Calibration is carried out by Tcc and Technet (Pictran B, D/E) software, using a special stand for calibration. Accuracy of half-scientific results is determined. Results of calibration are applied in processing photos. As a result of transformation of photos in plane in processing, they are applied to definition of influence of parameters of calibration and they do not affect the results of calibration of a camera. Photo in plane is transformed in 6 control points. The received results are visible in tables and figures. Accuracy of measurement of points in digital photo is certain. The results testify that digital camera Canon EOS 350D is very stable, an objective exact – interior parameters of calibration use small. The transformed, flat photos can be applied to research, designing and operation of engineering constructions. For exact works, it is recommended to correct photos for distortion of cameras.Article in Lithuanian.Skaitmeninės matuojamosios fotokameros kalibravimo parametrų įtaka nuotraukas transformuojant į plokštumąStraipsnyje aprašytas skaitmenines matuojamosios fotokameros Canon EOS 350D kalibravimo procesas, kurio metu nustatyti fotokameros vidinio orientavimo elementai – simetrine ir nesimetrine distorsijos. Kalibravimas atliktas Tcc ir Technet (Pictran B, D/E) programomis, naudojant specialu stenda su žinomomis tašku koordinatemis. Ivertintas gautu rezultatu tikslumas. Fotokameros kalibravimo rezultatai naudojami tolesniam nuotrauku apdorojimui. Siekiant nustatyti, kokios itakos fotokameros kalibravimo parametrai turi fotonuotrauku transformavimo i plokštuma rezultatams, atlikti skaičiavimai taikant fotokameros kalibravimo duomenis ir ju netaikant. Fotonuotraukos i plokštuma transformuotos pagal 6 kontrolinius taškus. Skaitmeninese fotonuotraukose ivertintas tašku matavimo tikslumas. Pateikta rezultatu apibendrinimas ir išvados.First published online: 03 Aug 2012